Resection of vaginal septum using endoscopic‐guided sealing devices in female dogs: 8 cases (2015–2018). (22nd December 2021) - Nicoli, S.; Caccamo, R.
Abstract : Objectives: Vestibulovaginal septal remnants are congenital anomalies that are often concurrent with ectopic ureters in bitches. During endoscopic laser ablation of the ectopic ureter, the vaginal septum should be cut in the same surgical session. However, sometimes, the septal length and thickness make the procedure extremely long and challenging with lasers. This study aimed to describe the use of sealing devices for septal cuts. Materials and Methods: We searched medical records for female dogs presented for ectopic ureters with endoscopic laser ablation that had a vaginal septum equal or longer than 4 cm in length that were treated using vesseal‐sealing devices. Results: Medical records of 37 patients were retrieved. Of those, 8 patients were eligible for inclusion in the case series. Weight of included dogs ranged from 10 to 27 kg, and age ranged from 3 to 60 months. Three of these patients had the septum resected using the LigaSure™ device, and five of them using the ENSEAL® device. The median time of septum resection using the vessel‐sealing devices was 100 seconds (range 60 to 130s). No obvious complications were detected when using the described technique. Clinical Significance: The sealing devices used by the authors allowed a rapid and uneventful resection of the vaginal septum in the cases described herein.